EFFECT OF HEALTH EDUCATION WITH DEMONSTRATION OF KNOWLEDGE OF INFANT MASSAGE IN GAMPING JATISAWIT IHC - Diah Hapsari Putri; Sri Widarti (Jurnal Kesehatan Karya Husada, 2015)
Background: Infant massage is the art of health care and treatment, known since the beginning of man created in the world and has been practiced since centuries - centuries of years ago is down - generation by TBAs. (Roesli, 2001). Benefits of infant massage that can increase the baby's weight, increase growth, increase endurance, increase milk production, improve blood circulation and respiration, reduce bloating and colic is caused by consuming milk formula, and reduce depression in infants. (Roesli, 2001).Objective: To know the effect of health education by the method of demonstration of knowledge of mothers about infant massage in Gamping Jatisawit IHC Yogyakarta 2014.Methods: Using a quasi experiment. The population in this study were all mothers - mothers in Gamping Jatisawit IHC 45 persons. The sampling technique used is non-probably sampling (purposive sampling), sampling is based on a certain consideration. (Sugiyono, 2010). The samples in this study were mothers - mothers with babies aged 0 months - 3 years.Result: There is an effect of health education with demonstration method to increase the knowledge of mothers about infant massage with the obtained p-value of 0.000.Conclusion: The level of knowledge of the mother after the given health education on infant massage demonstration method is better than before given health education.